2019
DOI: 10.1038/s41598-019-53725-x
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbal medicine for patients living with HIV in Guangxi province, China: an analysis of two registries

Abstract: Anti-Retroviral Therapy (ART) is the recommended first line therapy for patients with HIV. Since 2004, Chinese government has provided free Chinese herbal medicine (CHM) for Chinese HIV/AIDS patients. Data of living patients with HIV from the NFTCMP database and Center for Disease Control (CDC) database during 2003–2016 in Guangxi province was obtained and compared. Patients were divided into 3 groups according to their recorded treatment regimens. A total of 2954 patients with their treatment recorded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Sun et al [ 29 ] reported results of a retrospective cohort study including 2954 patients with HIV/AIDS. Patients were divided into three groups according to their recorded treatment regimens.…”
Section: Improving Laboratory Resultsmentioning
confidence: 99%
“…Sun et al [ 29 ] reported results of a retrospective cohort study including 2954 patients with HIV/AIDS. Patients were divided into three groups according to their recorded treatment regimens.…”
Section: Improving Laboratory Resultsmentioning
confidence: 99%
“…Unlike cART, TCM works on the overall immune function of patients; this approach is important because better immune function decreases the risk of opportunistic infection and tumor formation [18]. Many studies have reported their findings regarding the influence of TCM on the immune function of patients with AIDS, but their results are inconsistent [19][20][21]. e influence of TCM on the CD4 + T-cell count of patients with HIV/AIDS might be significantly related to the CD4 + T-cell count at the time of initial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…At present, in addition to the routine western medicine treatment, patients with HIV/AIDS in China, especially those who are intolerant of antiviral drugs or failed to antiviral therapy, will be treated with traditional Chinese herbal medicine to improve efficacy and reduce adverse reactions. [20] Although the evidence for the effectiveness and safety of this traditional Chinese and western medicine has been inconclusive, a growing body of studies have shown that this synergistic therapy combing Chinese herbal medicine with HAART has certain advantages in enhancing immunity, improving the quality of life, reducing the occurrence of serious opportunistic infections and alleviating bad effects caused by antivirals. [21] This study aimed to systematically investigate the efficacy and safety of Chinese herbal medicine in cooperation with HAART for HIV/AIDS and provide a reliable reference for the clinical application of Chinese medicine for HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first case of HIV/AIDS patient was discovered, Chinese clinicians and researchers have been committed to working on the TCM in the treatment of HIV/AIDS. At present, in addition to the routine western medicine treatment, patients with HIV/AIDS in China, especially those who are intolerant of antiviral drugs or failed to antiviral therapy, will be treated with traditional Chinese herbal medicine to improve efficacy and reduce adverse reactions [20] . Although the evidence for the effectiveness and safety of this traditional Chinese and western medicine has been inconclusive, a growing body of studies have shown that this synergistic therapy combing Chinese herbal medicine with HAART has certain advantages in enhancing immunity, improving the quality of life, reducing the occurrence of serious opportunistic infections and alleviating bad effects caused by antivirals [21] …”
Section: Discussionmentioning
confidence: 99%